Topological Electronic Structure and Intrinsic Magnetization in MnBi4Te7: A Bi2Te3 Derivative with a Periodic Mn Sublattice - Vidal, Raphael C.; Zeugner, Alexander; Facio, Jorge; Ray, Rajyavardhan; Haghighi, M. Hossein; Wolter, Anja U. B.; Bohorquez, Laura T. Corredor; Caglieris, Federico; Moser, Simon; Figgemeier, Tim; Peixoto, Thiago R. F.; Vasili, Hari Babu; et al. (Physical Review X, 2019)
Combinations of nontrivial band topology and long-range magnetic order hold promise for realizations of novel spintronic phenomena, such as the quantum anomalous Hall effect and the topological magnetoelectric effect. Following theoretical advances, material candidates are emerging. Yet, so far a compound that combines a band-inverted electronic structure with an intrinsic net magnetization remains unrealized. MnBi2Te4 has been established as the first antiferromagnetic topological insulator and constitutes the progenitor of a modular (Bi2Te3)n(MnBi2Te4) series. Here, for n=1, we confirm a nonstoichiometric composition proximate to MnBi4Te7. We establish an antiferromagnetic state below 13 K followed by a state with a net magnetization and ferromagnetic-like hysteresis below 5 K. Angle-resolved photoemission experiments and density-functional calculations reveal a topologically nontrivial surface state on the MnBi4Te7(0001) surface, analogous to the nonmagnetic parent compound Bi2Te3. Our results establish MnBi4Te7 as the first band-inverted compound with intrinsic net magnetization providing a versatile platform for the realization of magnetic topological states of matter.
CRIS-Team Scopus Importer:2022-04-14